Kinetic-physiotherapy diagnotics in women's health care: integrative review (Research, Society and Development, 2021)
The study aimed to discuss and analyze the kinetic-functional physiotherapeutic diagnoses in women's health care through an integrative review. The search was made in the VHL and PubMed portal with the search strategies and the descriptors physiotherapy, diagnosis, women's health, and evaluation. For the process of extracting data and information from the articles after reading them in their entirety, a self-created fiching instrument was used for this review. Eight search terms resulted in 147 findings, and with the inclusion and exclusion criteria of this review, 16 articles were chosen. It was evident that there are several kinetic-functional diagnoses and their contexts of application in physiotherapeutic care to women's health, and that their contribution is in the practice to enhance the information of health conditions and functional status of these individuals. It is recommended that future studies be conducted addressing greater specificities of the theme, such as kinetic-functional diagnosis in women's health in primary care. This kinetic-functional diagnosis, from the perspective of systematization, is a tool to contribute to the importance of assessment, intervention and physiotherapeutic.